Ectodermal Dysplasia - Connections and Implantation - P. Prachár; S. Bartáková; P. Černochová; J. Kuklová; J. Vaněk (Czech Dental Chamber, 2009)
Ectodermal dysplasia is a disease of strong familial disposition. There is a broad scale of subtypes with more or less expressed signs. The diagnostics is of high significance as well as the associated missing teeth. The shortage in dentition becomes apparent already in the primary teeth. In the permanent dentition hypodontia is significantly expressed and there are even cases anodontia.An insufficient bone matter is an important part of the problem. An interdisciplinary collaboration of several stomatology professions takes a part in the solution.In the final phase of therapy dental implantology can be used, specifically pedostomatology to orthodontia up to final prosthetic sanation.The authors provided an outline of the therapy of ectodermal dysplasia together with the individual approach to patients and implication of implants in the age category of youth and adolescents.